Genome Sequencing in the Parkinson Disease Clinic. (9th August 2022) - Hill, Emily J.; Robak, Laurie A.; Al-Ouran, Rami; Deger, Jennifer; Fong, Jamie C.; Vandeventer, Paul Jerrod; Schulman, Emily; Rao, Sindhu; Saade, Hiba; Savitt, Joseph M.; von Coelln, Rainer; Desai, Neeja; et al.
Abstract : Background and Objectives: Genetic variants affect both Parkinson disease (PD) risk and manifestations. Although genetic information is of potential interest to patients and clinicians, genetic testing is rarely performed during routine PD clinical care. The goal of this study was to examine interest in comprehensive genetic testing among patients with PD and document reactions to possible findings from genome sequencing in 2 academic movement disorder clinics. Methods: In 203 subjects with PD (age = 63 years, 67% male), genome sequencing was performed and filtered using a custom panel, including 49 genes associated with PD, parkinsonism, or related disorders, as well as a 90-variant PD genetic risk score. Based on the results, 231 patients (age = 67 years, 63% male) were surveyed on interest in genetic testing and responses to vignettes covering (1) familial risk of PD ( LRRK2 ); (2) risk of PD dementia ( GBA ); (3) PD genetic risk score; and (4) secondary, medically actionable variants ( BRCA1 ). Results: Genome sequencing revealed a LRRK2 variant in 3% and a GBA risk variant in 10% of our clinical sample. The genetic risk score was normally distributed, identifying 41 subjects with a high risk of PD. Medically actionable findings were discovered in 2 subjects (1%). In our survey, the majority (82%) responded that they would share a LRRK2 variant with relatives. Most registered unchanged or increased interest in testing when confronted with a potential risk for dementia or medically actionable findings, and most (75%) expressed interest in learning their PD genetic risk score. Discussion: Our results highlight broad interest in comprehensive genetic testing among patients with PD and may facilitate integration of genome sequencing in clinical practice.